P746Polyenoic fatty acids levels in essential hypertensive patients. (15th July 2014) - Dmitriev, V; Oschepkova, E; Titov, V
Abstract: Objective: Some authors were evidence for important pathogenic role of polyenoic fatty acids (PFA) in development of hypertension in alone experimental studies. The aim of our study was compare PFA levels in Essential hypertensive (EH) pts and healthy volunteers; evaluate association between PFA and Cholesterol and Triglyceride levels. Design and Methods: 50 EH pts (30 M, 20 F) grade 1 or 2, av. age 47, 0±1, 8 years; 10 healthy normotensive volunteers (6M, 4 F) av. age 48, 5 ± 3, 9 years (n/s). PFA (Eikosatetraenic, Eikosapentaenic, Dokosopentaenic, Dokosogeksaenic fatty acids) was defined by a method of gas chromatography. A Cholesterol (CH) and Triglyceride (TG) level was defined by enzymatic method. 60 % EH pts had high CH and 36 % high TG levels. High-sensitivity C-reactive protein (CRP) was defined by a method of turbidymetry. The statistical analysis was carried out by nonparametric methods of Mann-Whitney and Spearman with STATISTICA 6. The data is presented as M±SE. Results: The averages levels PFA in the EH pts were considerably higher compared to healthy group (Tab). In the EH pts was found positive association Cholesterol level with 20:04 (r=0, 33; p=0, 01), 20:05 (r=0, 37; p=0, 05), 22:06 (r=0, 48;p<0, 001) levels and Triglyceride level with 20:04 (r=0, 27; p=0, 05), 20:05 (r=0, 32; p<0, 05), 22:06 (r=0, 26;p=0, 05) levels. We didn't found significant association C-reactive protein, LDL and HDL level with polyenoic fatty acids levels. Conclusion: In our study high levels of polyenoic fatty acids was found in EH pts. Also we found significant association just between PFA, Cholesterol a Triglyceride levels. Parameters EH pts (n=50) HEalthy group (n=10) P value 20:04 (Eikosatetraenic FA) 136, 6±7, 1 89, 2±8, 4 p=0, 01 20:05 (Eikosapentaenic FA) 20, 4±1, 8 10, 7±1, 7 p=0, 01 22:05 (Dokosopentaenic FA) 9, 9±0, 7 6, 1±0, 9 p<0, 05 22:06 (Dokosogeksaenic FA) 58, 1±3, 6 35, 7±4, 5 p=0, 01 CRP (mg/L) 7, 5±1, 1 2, 7±0, 4 p<o, o5 24-h SBP (mm Hg) 137, 1±1, 8 118, 3±2, 8 p<0, 001 24-h DBP (mm Hg) 82, 8±1, 3 73, 9±2, 5 p<0, 05